2017
DOI: 10.1097/pts.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

A Report of Information Technology and Health Deficiencies in U.S. Nursing Homes

Abstract: Objective-Investigate the impact of nursing home information technology sophistication on publically reported health safety deficiency scores documented during standard inspections. Methods-The sample included 807 NHs from every US state. A total of 2187 health inspections were documented in these facilities. A national IT sophistication survey describing IT capabilities, extent of IT use, and degree of IT integration in resident care, clinical support, and administrative activities in US NHs was used. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 20 publications
(37 reference statements)
1
30
1
Order By: Relevance
“…The mix of negative evidence on training and productivity, versus positive evidence on staff communications and teamwork, may explain why we found no clear evidence that HIT enabled staff to improve quality of care. Alexander et al have found that higher HIT sophistication in NHs is associated with improved quality of resident care, 1 , 39 but it is not clear if HIT led to improvements, versus if the types of NHs that invest in more sophisticated HIT are also more likely to have higher quality of care. If HIT-related benefits are seen only in NHs with higher levels of staffing, this suggests that HIT adoption by other NHs may not produce the desired results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mix of negative evidence on training and productivity, versus positive evidence on staff communications and teamwork, may explain why we found no clear evidence that HIT enabled staff to improve quality of care. Alexander et al have found that higher HIT sophistication in NHs is associated with improved quality of resident care, 1 , 39 but it is not clear if HIT led to improvements, versus if the types of NHs that invest in more sophisticated HIT are also more likely to have higher quality of care. If HIT-related benefits are seen only in NHs with higher levels of staffing, this suggests that HIT adoption by other NHs may not produce the desired results.…”
Section: Discussionmentioning
confidence: 99%
“…Health information technology (HIT) systems have the potential to improve safety, communication, and productivity in nursing homes (NHs). Early research suggests HIT can improve scores on NH quality indices 1 ; resident outcomes such as maintenance of activities of daily living, range of motion, and bed mobility 2 ; and clinical support to reduce rates of adverse drug events and increase identification of medication errors. 3 , 4 The most recent survey of information technology (IT) in NHs reported that IT sophistication remains greatest for administrative support, such as billing functions, with growing incorporation in resident care functions such as bed availability and discharge management, and relatively slow uptake for clinical support functions such as documentation of vital signs, incident reporting, and medication administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent and current capabilities of health technology in LTCFs is limited owing to diverse organizational environment systems. As a result, gaining an understanding of its limits should be a prioritized objective, while an integration of sophisticated health technology systems into long-term care should be further emphasized [31].…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 federal report, Adverse Events in Skilled Nursing Facilities, estimated the cost of adverse events in NHs to be greater than 2.8 billion dollars and that two thirds of the adverse events that resulted in harm were preventable. Examples of adverse events identified by the report include medication errors, poor management of conditions, and preventable infections, among others (Office of the Inspector General, 2014).Previous research has shown that Health Information Technology (HIT) can improve quality of care and patient safety in a variety of health care settings, including some NHs (Alexander & Madsen, 2017;Kruse et al, 2017;Olsho et al, 2014; Rantz et al, 2010). HIT comprises an "array of computer applications for health care" to be used by health care providers, administrators, and patients for a variety of clinical and administrative functions, such as census management, billing, and maintaining and using electronic health records (EHRs;Richard et al, 2009).…”
mentioning
confidence: 99%